Prevalence of human papillomavirus genotypes in high‐grade cervical precancer and invasive cervical cancer from cancer registries before and after vaccine introduction in the United States. Issue 19 (21st July 2021) - Mix, Jacqueline M.; Saraiya, Mona; Thompson, Trevor D.; Querec, Troy D.; Greek, April; Tucker, Thomas C.; Peters, Edward S.; Lynch, Charles F.; Hernandez, Brenda Y.; Copeland, Glenn; Goodman, Marc T.; Unger, Elizabeth R.
Abstract : Background: US population‐based cancer registries can be used for surveillance of human papillomavirus (HPV) types found in HPV‐associated cancers. Using this framework, HPV prevalence among high‐grade cervical precancers and invasive cervical cancers were compared before and after HPV vaccine availability. Methods: Archived tissue from 2 studies of cervical precancers and invasive cervical cancers diagnosed from 1993‐2005 (prevaccine) were identified from 7 central cancer registries in Florida; Hawaii; Iowa; Kentucky; Louisiana; Los Angeles County, California; and Michigan; from 2014 through 2015 (postvaccine) cases were identified from 3 registries in Iowa, Kentucky, and Louisiana. HPV testing was performed using L1 consensus polymerase chain reaction analysis. HPV‐type–specific prevalence was examined grouped by hierarchical attribution to vaccine types: HPV 16, 18, HPV 31, 33, 45, 52, 58, other oncogenic HPV types, and other types/HPV negative. Generalized logit models were used to compare HPV prevalence in the prevaccine study to the postvaccine study by patient age, adjusting for sampling factors. Results: A total of 676 precancers (328 prevaccine and 348 postvaccine) and 1140 invasive cervical cancers (777 prevaccine and 363 postvaccine) were typed. No differences were observed in HPV‐type prevalence by patient age between the 2 studies among precancers or invasive cancers. Conclusions: The lack of reduction in vaccine‐type prevalence between the 2 studies is likely explained by the low number of cases and low HPV vaccination coverage among women in the postvaccine study. Monitoring HPV‐type prevalence through population‐based strategies will continue to be important in evaluating the impact of the HPV vaccine. Abstract : In this study, a reduction in human papillomavirus (HPV) prevalence from a prevaccine period to a postvaccine period was not observed, likely attributable to a low number of cases and low HPV‐vaccination coverage in the postvaccine period. However, using the framework for obtaining HPV‐genotyping information from population‐based cancer registries could be an important strategy for monitoring HPV prevalence and impact of the HPV vaccine, particularly in younger women who are more likely to have been vaccinated.